Age-Related Decrease in Male Extra-Striatal Adenosine A1 Receptors Measured Using11C-MPDX PET - Mishina, Masahiro; Kimura, Yuichi; Sakata, Muneyuki; Ishii, Kenji; Oda, Keiichi; Toyohara, Jun; Kimura, Kazumi; Ishiwata, Kiichi (Frontiers in Pharmacology, 2017)
Adenosine A1 receptors (A1Rs) are widely distributed throughout the entire human brain, while adenosine A2A receptors (A2ARs) are present in dopamine-rich areas of the brain, such as the basal ganglia. A past study using autoradiography reported a reduced binding ability of A1R in the striatum of old rats. We developed positron emission tomography (PET) ligands for mapping the adenosine receptors and we successfully visualized the A1Rs using 8-dicyclopropylmethyl-1-11C-methyl-3-propylxanthine (11C-MPDX). We previously reported that the density of A1Rs decreased with age in the human striatum, although we could not observe an age-related change in A2ARs. The aim of this study was to investigate the age-related change of the density of A1Rs in the thalamus and cerebral cortices of healthy participants using 11C-MPDX PET. We recruited eight young (22.0 ± 1.7 years) and nine elderly healthy male volunteers (65.7 ± 8.0 years). A dynamic series of decay-corrected PET scans was performed for 60 min starting with the injection of 11C-MPDX. We placed the circular regions of interest of 10 mm in diameter in 11C-MPDX PET images. The values for the binding potential (BPND) of 11C-MPDX in the thalamus, and frontal, temporal, occipital, and parietal cortices were calculated using a graphical analysis, wherein the reference region was the cerebellum. BPND of 11C-MPDX was significantly lower in elderly participants than young participants in the thalamus, and frontal, temporal, occipital, and parietal cortices. In the human brain, we could observe the age-related decrease in the distribution of A1Rs.